Images of language in middle english vernacular writings - CAWSEY, KATHY ([Place of publication not identified] D S BREWER, 2020)
An exploration of the use of images in Middle English texts, tracing out what can be deduced of a theory of language.
Introduction -- 1 Vernacular Transformation of the Latin Inheritance: Chaucer's House of Fame -- 2 Depictions of Oral Language: The Owl and the Nightingale -- 3 Ideas of Written Language: Merlin's Magical Writing -- 4 Metaphors of Language and Power: The Tutivillus Tales -- 5 Disrupting the Power Structures of Language: Wheat and Chaff -- Conclusions.
Includes bibliographical references (pages 181-197) and index.
JSTOR
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Philosophy of language; LANGUAGE ARTS & DISCIPLINES / General; English literature -- Middle English; 1100-1500; Chaucer; Malory; nightingale; owl; Electronic books; Criticism, interpretation, etc